Coregonus nasus ... - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
Coregonus nasus (Pallas, 1776). Broad Whitefish. To 83.5 cm (32.8 in) TL (George et al. 2007; confirmed by Lawrence Moulton, pers. comm.). Arctic coasts from Siberia to Queen Maud Gulf, Nunavut (Harris in Coad and Reist 2018); Beaufort, Chukchi, and Bering drainages of Alaska south to Kuskokwim Bay. Primarily in fresh water, not venturing far seaward in brackish water (Mecklenburg et al. 2002). Some authors (e.g., Reist in Coad and Reist 2018) consider this a species or subspecies complex. ... : Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 53, DOI: 10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008 ...